The Determination of Levels of Active Listening Competencies of Pre-service Teachers - Kazu, Hilal; Demiralp, Demet (Kamla-Raj Enterprises, 2015)
By determining the levels of active listening competencies of pre-service teachers, this study aims to compare these levels in terms of a wide range of variables. This research is designed in accordance with a survey model. The sample of the study consists of 672 pre-service teachers studying as senior students in their own departments in the Faculty of Education at Firat University. The findings reveal that the pre-service teachers have most of the active listening competencies in the 'usually' level. In the study, when the pre-service teachers' level of active listening competencies have been observed as regards to the gender variable, it has been determined that female candidates are more likely to show the note taking listening competency. In addition, it has been observed that they frequently nod their head to the meaning of 'I see' while listening. Furthermore, the pre-service teachers in the verbal field display higher levels of active listening competencies.
Keywords: Active Listening; Communication; Effective Listening; Listening Skills; Teacher Education